FUZZY-LIKERT SCALE BASED ASSESSMENT OF MARKETING RISK FACED BY THE HYBRID RICE GROWERS OF BANGLADESH - Pervez, A. K. M. Kanak; Uddin, 2 Md. Ektear; Ahmad Shah, Ashfaq; Ahmed Prodhan, Foyez; Sheikh, Md. Mohiuddin (Economics of Agriculture, 2019)
The primary concentration of this study was to assess the marketing risks faced by hybrid rice growers and explore the trajectories. With this notion, data were collected from randomly selected 300 hybrid rice growers in purposively chosen areas with the application of a structured interview schedule and conducting five focus group discussions with the farmers. The study identified seven key risks responsible for the poor marketing of hybrid rice in Bangladesh. Perceived marketing risks were assessed by farmers opinion on likelihood and severity of each risk source through using a fuzzy-Likert scale. According to the finding high fluctuation of hybrid rice price was the most serious risk in hybrid rice marketing in Bangladesh. The regression result found several socio-demographic factors of the farmers are significantly related with perceived risk. This study, therefore, suggests government taking pro policies for hybrid rice growers organized around farmers those socio-demographic characteristics for minimizing marketing risk.